PEMANFAATAN DAN PENGELOLAAN SAMPAH DAUN MANGGA SEBAGAI PUPUK KOMPOS DI DESA ORO-ORO OMBO, KECAMATAN REMBANG, KABUPATEN PASURUAN - Haidar Fari Aditya; Ramadhani Mahendra Kusuma; Wiwin Windriyanti; Mochamad Arifin (Gapenas Publisher, 2022)
Community service activities in the form of introducing technology in the manufacture of compost made from mango leaves are an effort to take advantage of the potential that exists in the surrounding environment in the form of remnants of organic waste that will be used as fertilizer. This community service activity was carried out in Oro-Oro Ombo Village, Rembang District, Pasuruan Regency. The method used in this activity is provision of learning materials in the form of socialization and demonstration. Providing training materials on the manufacture of organic fertilizer made from mango leaves. Demonstration activities were carried out by practicing organic fertilizers and introducing the tools and materials used which were directly guided by the lecturers of the Faculty of Agriculture, UPN